A COVID-19 Hotspot Area: Activities and Epidemiological Findings - Francesca Cito; Laura Amato; Alessandra Di Giuseppe; Maria Luisa Danzetta; Simona Iannetti; Antonio Petrini; Alessio Lorusso; Barbara Bonfini; Alessandra Leone; Romolo Salini; Adamo Mancinelli; Giuseppe Torzi; et al. (Microorganisms, 2020)
By late March 2020, Villa Caldari, a small village of the municipality of Ortona (Abruzzo region), was registering an incidence rate of COVID-19 cases ten times greater than the overall municipality and was declared a hotspot area. Twenty-two days later, epidemiological investigation and sampling were performed, to evaluate SARS-CoV-2 circulation and the presence of SARS-CoV-2 antibodies. Overall, 681 nasopharyngeal swabs and 667 blood samples were collected. Only one resident of the village resulted in being positive for RNA viral shedding, while 73 were positive for SARS-CoV-2 antibodies. The overall seroprevalence was 10.9%. The difference between the seroprevalence of infection in asymptomatic and symptomatic individuals was significant (χ2 = 14.50 p-value = 0.0001). Amongst the residents positive for antibodies, fatigue and/or muscle pain, fever and anosmia were the most experienced symptoms, whose most frequent onset was observed during the first two weeks of March. Familial and habit-related clusters were highlighted. Nevertheless, the investigations showed a low SARS-CoV-2 circulation in the village at the time of the sampling, demonstrating virus transmission could be limited when strict emergency measures are followed. Given the favorable results, the emergency measures were then lifted.